Crustal structure beneath the Blue Mountains terranes and cratonic North America, eastern Oregon, and Idaho, from teleseismic receiver functions. Issue 7 (12th July 2016) - Christian Stanciu, A.; Russo, Raymond M.; Mocanu, Victor I.; Bremner, Paul M.; Hongsresawat, Sutatcha; Torpey, Megan E.; VanDecar, John C.; Foster, David A.; Hole, John A.
Abstract: We present new images of lithospheric structure obtained from P ‐to‐ S conversions defined by receiver functions at the 85 broadband seismic stations of the EarthScope IDaho‐ORegon experiment. We resolve the crustal thickness beneath the Blue Mountains province and the former western margin of cratonic North America, the geometry of the western Idaho shear zone (WISZ), and the boundary between the Grouse Creek and Farmington provinces. We calculated P ‐to‐ S receiver functions using the iterative time domain deconvolution method, and we used the H‐k grid search method and common conversion point stacking to image the lithospheric structure. Moho depths beneath the Blue Mountains terranes range from 24 to 34 km, whereas the crust is 32–40 km thick beneath the Idaho batholith and the regions of extended crust of east‐central Idaho. The Blue Mountains group Olds Ferry terrane is characterized by the thinnest crust in the study area, 24 km thick. There is a clear break in the continuity of the Moho across the WISZ, with depths increasing from 28 km west of the shear zone to 36 km just east of its surface expression. The presence of a strong midcrustal converting interface at 18 km depth beneath the Idaho batholith extending 20 km east of the WISZ indicates tectonic wedging in this region. A north striking 7 km offset in Moho depth, thinning to the east, is present beneath the Lost River Range and Pahsimeroi Valley; we identify this sharp offset as the boundary that juxtaposes the Archean Grouse Creek block with the Paleoproterozoic Farmington zone. Key Points: Strongly varying crustal thickness beneath the Blue Mountains accreted terranes and cratonic North America Two major Moho offsets, the western Idaho shear zone, and the Grouse Creek‐Farmington zone boundary Midcrustal converter at 18 km depth indicates tectonic wedging of Blue Mountains into North American crust